Deducing the Conformational Properties of a Tyrosine Kinase Inhibitor in Solution by Optical Spectroscopy and Computational Chemistry - Kabir, Md. Lutful; Backler, Frederick; Clayton, Andrew H. A.; Wang, Feng (Frontiers in Chemistry, 2020)
Dacomitinib (PF-00299804) was recently approved by the Food and Drug Administration (FDA) as a tyrosine kinase inhibitor (TKI). Unfortunately, side effects and disease resistance eventually result from its use. Off-target effects in some kinase inhibitors have arisen from drug conformational plasticity; however, the conformational states of Dacomitinib in solution are presently unknown. To fill this gap, we have used computational chemistry to explore optimized molecular geometry, properties, and ultraviolet-visible (UV-Vis) absorption spectra of Dacomitinib in dimethyl sulfoxide (DMSO) solution. Potential energy scans led to the discovery of two planar and two twisted conformers of Dacomitinib. The simulated UV-Vis spectral signatures of the planar conformers reproduced the two experimental spectral bands at 275 and 343 nm in solution. It was further discovered that Dacomitinib forms conformers through its three flexible linkers of two C–NH–C bridges, which control the orientations of the 3-chloro-4-fluoroaniline ring (Ring C) and the quinazoline ring (Rings A and B) and the 4-piperidin-1-yl-buten-2-nal side chain, and one C–O–C local bridge which controls the methoxy group locally. When in isolation, these flexible linkers form close hexagon and pentagon loops through strong intramolecular hydrogen bonding so that the “planar” conformers Daco-P1 and Daco-P2 are more stable in isolation. Such flexibility of the ligand and its ability to dock and bind with protein also depend on their interaction with the environment, in addition to their energy and spectra in isolation. However, an accurate quantum mechanical study on drug/ligand conformers in isolation provides necessary reference information for the ability to form a complex with proteins.